Oil-proof coating composition for paper products and application of oil-proof coating composition

By using an oil-resistant coating composition combining dendritic or network-like biomass materials and other degradable materials, the problem of insufficient surface strength and waterproof and oil-proof performance of paper plastic products is solved, and environmentally friendly and economical oil-proofing is achieved and reduces environmental pollution.

CN119266000APending Publication Date: 2025-01-07HANGZHOU GREEN MICRO-NANO TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411486474.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Due to the fiber structure, existing paper and plastic products have low surface strength, poor wear resistance, extremely poor waterproof and oil-proof performance, and the use of petroleum-based materials cannot naturally degrade, affecting environmental protection and recycling.

Method used

Use biomass materials with dendritic or network-like structures and cationic biomass materials with PHA, AKD, PLA, PBAT, cellulose ester and other materials, and combine beeswax, palm wax, modified starch, etc. to form an oil-proof coating combination The substance is prepared by vacuum stirring and hot air drying technology to form dense micro-nano structures to improve oil resistance.

Benefits of technology

The oil-resistant coating without petroleum-based polymer materials is realized, and the biomass materials are closely connected to paper products, which significantly improves the oil-proof effect, and is simple in process and low in cost, which meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119266000A_ABST
    Figure CN119266000A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of paper products such as paper and paper plastic, and particularly relates to an oil-proof coating composition for paper products and application of the oil-proof coating composition for the paper products, the coating composition comprises a component A and a component B, the component A is one or more of a biomass material with a dendritic or network structure or a cationized biomass material with a dendritic or network structure; the component B is selected from one, two or more of polyhydroxyalkanoate, alkyl ketene dimer, polyglycolide, polylactide, copolymer of butylene adipate and butylene terephthalate, cellulose ester and cellulose ether; the component C is selected from one, two or more of beewax, palm wax, vegetable wax, modified starch, montmorillonite and lamellar clay. The oil-proof coating composition disclosed by the invention does not contain non-degradable petroleum-based high polymer materials, and the components of the oil-proof coating composition are degradable materials in a natural environment, so that the oil-proof coating composition is relatively environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of paper products such as paper and paper plastic, and in particular relates to an oil-proof coating composition for paper products and application thereof. Background Art

[0002] Pulp molded products (hereinafter referred to as paper plastics) are mainly made of fiber raw materials (such as wood, bagasse or bamboo), supplemented with non-fiber raw materials (such as reinforcing agents, water repellents, oil repellents, coatings, etc.), and are formed by hot pressing with molding molds. Paper plastic products are gradually replacing foams, plastics, etc. due to their low price and environmental protection, and are widely used in the manufacture of tableware, product packaging, fruit and egg transport trays and other products. However, due to their own structural characteristics, paper plastic products are loose and porous, have poor barrier properties, lack surface strength and smoothness, have low surface strength, poor wear resistance, and are easy to fall off and fall off. The appearance is inferior to other plastics and foams, and the waterproof and oil-proof properties are extremely poor. This is related to the fiber characteristics of pulp. The roughness of the fiber surface and its easy water absorption make the prepared products have certain limitations in these aspects.

[0003] In order to improve the waterproof and oil-proof performance of paper-plastic products, the method of in-slurry sizing is usually adopted to expand the use scenarios of paper-plastic products. The addition of non-fiber raw materials can easily cause mold sticking and block the mold holes during production, requiring frequent mold removal and cleaning, affecting production efficiency. Moreover, this sizing method can only cope with usage scenarios with low requirements for waterproof and oil-proof performance. It is almost impossible to apply it to situations where paper straws, disposable tableware, paper vases, etc. need to be in direct contact with water and oil. Therefore, applying a protective coating on the surface of paper-plastic products to improve the waterproof and oil-proof performance has become a relatively popular treatment method.

[0004] At present, the industry usually adopts the method of covering with polyolefin film, spraying polyacrylate or polystyrene emulsion and other synthetic materials to improve it. Although this method can meet the current usage needs, the introduction of these petroleum-based materials and artificial synthetic polymers will cause paper-plastic products to be unable to achieve true natural degradation, and recycling and reuse are also very difficult. Ultimately, a large amount of microplastic substances will be produced in nature, which not only brings serious harm to the natural environment and human survival, but also does not meet the current objective requirements of green packaging and low-carbon development. Summary of the invention

[0005] In order to improve the deficiencies of the prior art, the present invention provides an oil-proof coating composition for paper products, the coating composition comprising:

[0006] Component A: one or more of a biomass material having a dendritic or network structure or a cationized biomass material having a dendritic or network structure;

[0007] Component B is one, two or more selected from PHA (polyhydroxyalkanoate), AKD (alkyl ketene dimer), PGA (polyglycolide), PLA (polylactide), PBAT (copolymer of butylene adipate and butylene terephthalate), cellulose ester and cellulose ether, for example, a combination of PHA and AKD;

[0008] Component C is one, two or more selected from beeswax, palm wax, vegetable wax, modified starch, montmorillonite and lamellar clay.

[0009] According to an embodiment of the present invention, the paper product includes paper and paper plastic.

[0010] According to an embodiment of the present invention, in parts by weight, the oil-proof coating composition comprises 1-10 parts of component A, 5-20 parts of component B, and 5-20 parts of component C, and is preferably composed of them. Preferably, the oil-proof coating composition comprises 3-6 parts of component A, 10-20 parts of component B, and 15-20 parts of component C, and is preferably composed of them. For example, the oil-proof coating composition consists of 1 part of component A, 10 parts of component B, and 10 parts of component C.

[0011] As an example, the component A is a biomass material having a dendritic or network structure.

[0012] As another example, the component A is a cationized biomass material having a dendritic or network structure.

[0013] As another example, the component A consists of a biomass material having a dendritic or network structure and a cationized biomass material having a dendritic or network structure.

[0014] According to an embodiment of the present invention, when the component A is composed of a biomass having a dendritic or network structure and a cationized biomass material having a dendritic or network structure, the mass ratio of the biomass having a dendritic or network structure to the cationized biomass material having a dendritic or network structure is (1 to 5):1. For example, in parts by weight, the component A is composed of 2 parts of biomass having a dendritic or network structure and 1 part of a cationized biomass material having a dendritic or network structure.

[0015] According to an embodiment of the present invention, the component B is selected from one, two or more of PHA (polyhydroxyalkanoate), AKD (alkyl ketene dimer), cellulose ester and cellulose ether, preferably selected from one, two or more of PHA, AKD, cellulose ester and cellulose ether.

[0016] According to an embodiment of the present invention, the component C is selected from one, two or more of beeswax, palm wax, vegetable wax, modified starch and montmorillonite, preferably selected from one, two or more of beeswax, palm wax, modified starch and montmorillonite.

[0017] According to an embodiment of the present invention, the modified starch is selected from one or more of oxidized starch, etherified starch and acetylated starch.

[0018] According to an embodiment of the present invention, the degree of substitution of the modified starch is greater than or equal to 0.1, preferably the degree of substitution of the modified starch is greater than or equal to 0.2, for example, 0.2 or 0.3.

[0019] The present invention also provides a method for preparing a coating composition slurry, comprising the following steps:

[0020] The coating composition as described above is mixed with a solvent to obtain a coating composition slurry.

[0021] According to an embodiment of the present invention, the mass ratio of the coating composition to the solvent is 1:(1-10), preferably the mass ratio of the coating composition to the solvent is 1:(1-8).

[0022] According to an embodiment of the present invention, the solvent is selected from one or a mixture of two or more of water, alcohol and ethyl acetate, and preferably the solvent is deionized water.

[0023] According to an embodiment of the present invention, the mixing is performed under vacuum conditions.

[0024] According to an embodiment of the present invention, the mixing is performed under stirring conditions.

[0025] According to an embodiment of the present invention, the stirring rate is 500-3000 rpm, and the stirring time is 5-60 min, for example, stirring at a speed of 500 rpm for 30 min.

[0026] As an example, the preparation method includes the following steps: weighing 1 part of component A, 10 parts of component B, and 10 parts of component C in sequence, adding them into a stirring tank, then adding 70 parts of deionized water, sealing the stirring tank, vacuum stirring for 30 minutes, and unloading into a storage barrel to obtain a coating composition slurry.

[0027] The present invention also provides application of the coating composition as an oil-proof coating for paper products.

[0028] The present invention also provides a method for applying the above-mentioned oil-proof coating composition on the surface of a paper product, comprising the following steps:

[0029] The oil-proof coating composition slurry as described above is coated on at least one surface of a paper product material that can form a substrate to form an oil-proof coating layer.

[0030] According to an embodiment of the present invention, the coating is selected from conventional coating means in the art, such as machine coating or spray coating.

[0031] According to an embodiment of the present invention, the coating amount is 10-30 g / m 2 , the drying temperature is 80-150°C.

[0032] According to an embodiment of the present invention, after the water-based coating is applied to the surface of the material capable of forming the substrate, a drying step is further included, wherein the drying includes at least one of hot air drying or hot press drying.

[0033] The present invention also provides a paper product with an oil-proof coating, which comprises a substrate and an oil-proof coating located on at least one surface of the substrate.

[0034] According to an embodiment of the present invention, the pulp product is a paper product.

[0035] Beneficial Effects

[0036] 1) The oil-proof coating composition of the present invention does not contain non-degradable petroleum-based polymer materials, and its components are all degradable materials in the natural environment, which is relatively environmentally friendly.

[0037] 2) The biomass material in the oil-proof coating composition of the present invention is selected from one or both of biomass materials with dendritic or network structures or cationized biomass materials with dendritic or network structures. The dendritic or network structures in the biomass materials have rich micro-nano multi-level structures, which can be overlapped to form a dense network, and a large number of hydroxyl groups are distributed on the micro-nano structures. These hydroxyl groups can form hydrogen bonds or chemical bonds with cellulose in paper and plastic products, so that the coating is closely connected to the paper product, and the coating is prevented from peeling off from the surface of the paper product under high heat or external force. Thanks to its special micro-nano multi-level structure, a small amount of addition can obtain a significant comprehensive effect, and the preparation process of the biomass is simple and energy consumption is low.

[0038] 3) The oil-proof coating composition of the present invention is coated on a paper product by an existing coating method and dried to obtain a paper-plastic product with an oil-proof coating. The operation method is relatively simple and the cost is relatively low.

[0039] 4) The paper product with the oil-proof coating in the present invention has a good oil-proof effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is the SEM image of the biomass material in Example 1;

[0041] Figure 2 The oil-proof test results of existing disposable food packaging paper, commercial paper products, and the oil-proof paper corresponding to Example 3; and the oil penetration test chart of blank paper and the oil-proof paper corresponding to Example 3. DETAILED DESCRIPTION

[0042] [Structure of biomass materials with dendritic or network structures]

[0043] The biomass material with a dendritic or network structure includes a micron-scale structure and a nanometer-scale structure distributed on the micron-scale structure.

[0044] According to an embodiment of the present invention, the biomass material with a dendritic or network structure is a regenerated natural polymer (for example, type II cellulose, or a mixture of type II cellulose and type I cellulose), and the regenerated natural polymer includes a micron-scale structure and a nanoscale structure distributed on the micron-scale structure.

[0045] According to an embodiment of the present invention, the size of the micron-scale structure (i.e., the volume average size) is 50μm to 500μm, preferably the size of the micron-scale structure is 50μm to 300μm, and further preferably, the size of the micron-scale structure is 100μm to 200μm, for example, any value among 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, or any point value among the intermediate values ​​formed by any two point values.

[0046] According to an embodiment of the present invention, the length of the nanoscale structure is 50nm to 800nm, preferably the length of the nanoscale structure is 100nm to 500nm, and further preferably, the length of the nanoscale structure is 200nm to 400nm, for example, any value among 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm or any point value in the middle value formed by any two point values.

[0047] According to an embodiment of the present invention, the aspect ratio of the nanoscale structure is 1:1 to 1:150, preferably the aspect ratio of the nanoscale structure is 1:1 to 1:100, more preferably the aspect ratio of the nanoscale structure is 1:10 to 1:100, for example 1:50.

[0048] According to an embodiment of the present invention, the micron-scale structure includes at least one of a micron sheet, a micron fiber, and a micron multi-level structure.

[0049] According to an embodiment of the present invention, the micron-scale structure is in a fiber or film shape, which can also be called fiberization.

[0050] According to an embodiment of the present invention, the nanoscale structures are distributed on the surface and / or edge of the microscale structure. Specifically, the nanoscale structures are densely distributed on the surface and / or edge of the microscale structure.

[0051] According to an embodiment of the present invention, the nano-scale structure is distributed on the micro-scale structure to form a flocculent shape as a whole.

[0052] According to an embodiment of the present invention, the nano-scale structure is distributed on the micro-scale structure to form an overall structure similar to a porous sponge.

[0053] According to an embodiment of the present invention, the nano-scale structure and the micro-scale structure together form a feather-like structure.

[0054] According to an embodiment of the present invention, the nanoscale structure is in the shape of villi, tentacles, whiskers or other irregular structures.

[0055] According to an embodiment of the present invention, the biomass material is in a fibrous, flaky, feathery, branchy, flocculent or porous sponge-like structure.

[0056] [Preparation of biomass materials with dendritic or network structures]

[0057] The preparation method is selected from method 1 or method 2, wherein the method 1 comprises the following steps:

[0058] dissolving the biomass in a solvent to form a biomass solution;

[0059] The biomass solution and the coagulation bath are added to a crushing device, and the two are mechanically crushed while being mixed to prepare the bio-based material; or after the mechanical crushing, the biomass material with a dendritic or network structure is prepared by filtering and washing;

[0060] The second method comprises the following steps: pouring the biomass solution into a coagulation bath to form a biomass gel; and subjecting the biomass gel to micro-nano treatment through mechanical crushing to obtain the biomass material with a dendritic or network structure.

[0061] According to an embodiment of the present invention, the reagent used in the washing step in method one and method two is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.

[0062] According to an embodiment of the present invention, the biomass is derived from one, two or more of the following substances: cellulose or its derivatives (such as ethyl cellulose, carboxymethyl cellulose, cellulose acetate), starch or its derivatives (such as oxidized starch, modified oil-proof starch), chitosan or its derivatives (such as carboxymethyl chitosan, chitin), and alginate.

[0063] According to an embodiment of the present invention, the biomass is selected from at least one of lignin, glucan, hemicellulose, straw, plant stems and leaves, reeds, bagasse, Chinese medicine residues, tea residues, corn cobs, fruit shells, vines, branches and the like.

[0064] For example, the biomass is selected from at least one of microcrystalline cellulose, bacterial cellulose, lignin, cotton pulp, wood pulp, bamboo pulp, straw pulp, refined cotton, absorbent cotton, cotton linter, bagasse, wood and straw, etc.; preferably one or more of microcrystalline cellulose, refined cotton, absorbent cotton and wood pulp.

[0065] According to an embodiment of the present invention, the solvent for dissolving the biomass can be selected from any good solvent known in the art that can completely dissolve the biomass. Preferably, according to the different types of cellulose or cellulose-containing raw materials, the selected solvent can be selected from one or more of the following systems: organic solvents, ionic liquids, mixed solvents of ionic liquids and organic solvents, choline-type ionic liquid low eutectic solvent systems, organic solvent / salt systems, amine oxide systems (NMMO), carbamate systems, alkali / water systems, alkali / urea systems, alkali / thiourea systems, liquid ammonia / NH4SCN, organic acids, aqueous solutions of metal salts, alcohol solutions of metal salt hydrates, water-alcohol mixed solutions of metal salt hydrates, and other solvent systems.

[0066] According to an embodiment of the present invention, the coagulation bath is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.

[0067] For example, the biomass material can be obtained by the preparation method described in the patent document application with application number 202310481795.1.

[0068] [Preparation of cationized biomass materials with dendritic or network structures]

[0069] [Cationized biomass materials with dendritic or network structures]

[0070] According to an embodiment of the present invention, the cationized biomass material structure having a dendritic or network structure modified by an organic ammonium substance containing a halogenated hydrocarbon group or an epoxy group has a rich micro-nano multi-level structure, can be grafted to form a dense network at a certain temperature and time, and a large number of hydroxyl groups are distributed on the micro-nano structure to form a larger network structure.

[0071] [Preparation of cationized biomass materials with dendritic or network structures]

[0072] A biomass material solution with a dendritic or network structure is added to an alkaline aqueous solution, stirred and dissolved to obtain a biomass alkaline solution, an alcohol organic solvent is added to the biomass alkaline solution to dissolve, a cationic etherifying agent is added to carry out a grafting reaction, and washed to obtain a cationic biomass material with a dendritic or network structure.

[0073] According to an embodiment of the present invention, the alkaline aqueous solution is selected from a NaOH aqueous solution and / or a KOH aqueous solution, and the concentration of the alkaline aqueous solution is 0.1% to 3%.

[0074] According to an embodiment of the present invention, the mass concentration of the biomass having a dendritic or network structure in the alkaline solution is 2% to 10%.

[0075] According to an embodiment of the present invention, the biomass having a dendritic or network structure is reacted in an alkaline solution at a temperature of 30 to 60° C. and a reaction time of 1 to 5 hours.

[0076] According to an embodiment of the present invention, the mass ratio of the biomass alkali solution to the etherifying agent alcohol solution is 1:0.5 to 1:3.

[0077] According to an embodiment of the present invention, the cationic etherifying agent is selected from organic ammonium salts containing halogenated hydrocarbon groups or epoxy groups, such as one or more of 3-chloro-2-hydroxypropyl-trimethylammonium chloride and epoxypropyltrimethylammonium chloride.

[0078] According to an embodiment of the present invention, the alcohol organic solvent is a composite solvent of one or more of methanol, ethanol and isopropanol.

[0079] According to an embodiment of the present invention, the temperature of the grafting reaction is 25 to 75° C., and the reaction time is 6 to 48 hours.

[0080] According to an embodiment of the present invention, the grafting reaction is carried out under stirring conditions.

[0081] The following will be further described in detail with reference to specific examples of the general formula compound of the present invention and its preparation method and application. It should be understood that the following examples are only for exemplary description and explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0082] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0083] Example 1

[0084] An oil-proof coating composition comprising:

[0085] Component A1: 1g of biomass material with a dendritic or network structure;

[0086] Preparation of biomass material: 3.5 parts of wood pulp are dissolved in 75 parts of 1-ethyl-3-methylimidazole acetate, stirred at 65°C for 5 hours to form a biomass solution; the above biomass solution and 30 parts of water are added to a crushing device, and the two are mechanically crushed while mixing, and the ionic liquid is filtered and washed to prepare a biomass material with a solid content of 2.3% and a size of 20μm to 35μm with a dendritic or network structure.

[0087] Component B 10 parts: 9g PHA, 1g AKD;

[0088] Component C 10 parts: 4g palm wax, 4g oxidized starch (substitution degree 0.2), and 2g montmorillonite.

[0089] The oxidized starch in component C comes from Zhucheng Xingmao Corn Development Co., Ltd.

[0090] Oil-proof coating composition slurry: add 1g of biomass material with a dendritic or network structure, 9g of PHA, 1g of AKD, 4g of palm wax, 4g of modified starch, and 2g of montmorillonite into a stirring tank, then add 79g of deionized water, seal the stirring tank, vacuum stir for 30min, and discharge into a storage barrel to obtain a coating composition slurry.

[0091] Example 2

[0092] An oil-proof coating composition comprising:

[0093] Component A2: 2 g of biomass material with a cationic dendritic or network structure;

[0094] Preparation of cationic biomass material: Add 2 parts of the biomass material with a dendritic or network structure in Example 1 to 150 parts of a 0.15% NaOH aqueous solution, stir at room temperature for 2 hours to obtain a biomass alkali solution, add 20 parts of anhydrous ethanol to the biomass alkali solution, and then add 1.5 parts of 2,3-epoxypropyltrimethylammonium chloride, stir and react at 40°C for 12 hours. After the reaction is completed, wash with water to neutrality to obtain a cationic biomass material with a dendritic or network structure of 20μm to 35μm and a solid content of 1.5%.

[0095] Component B 15 parts: 15g PHA;

[0096] Component C 10 parts: 4g palm wax, 4g etherified starch (substitution degree 0.1), and 2g montmorillonite.

[0097] The etherified starch in component C comes from Langfang Longteng New Materials Co., Ltd. (hydroxymethyl starch ether).

[0098] Oil-proof coating composition slurry: add 2g of cationic biomass material with a dendritic or network structure, 15g of PHA, 4g of palm wax, 4g of modified starch, and 2g of montmorillonite into a stirring tank, then add 73g of deionized water, seal the stirring tank, vacuum stir for 30min, and discharge into a storage barrel to obtain a coating composition slurry.

[0099] Example 3

[0100] An oil-proof coating composition comprising:

[0101] Component A2: 1g of biomass material with a dendritic or network structure, 1g of cationized biomass material with a dendritic or network structure;

[0102] Preparation of biomass material: 1 g of the biomass material with a dendritic or network structure prepared in Example 1 and 1 g of the cationic biomass material with a dendritic or network structure prepared in Example 2 were mixed, and high-speed dispersed at 1200 rpm for 8 min to obtain a uniformly mixed biomass material.

[0103] Component B11 parts: 10g PHA, 1g AKD;

[0104] Component C 10 parts: 4g palm wax, 4g oxidized starch (substitution degree 0.2), and 2g montmorillonite.

[0105] The oxidized starch in component C comes from Zhucheng Xingmao Corn Development Co., Ltd.

[0106] Oil-proof coating composition slurry: add 1g of biomass material with a dendritic or network structure, 1g of cationized biomass material with a dendritic or network structure, 10g of PHA, 1g of AKD, 4g of palm wax, 4g of modified starch, and 2g of montmorillonite into a stirring tank, then add 78g of deionized water, seal the stirring tank, stir under vacuum for 30min, and discharge the material into a storage barrel to obtain a coating composition slurry.

[0107] Example 4

[0108] An oil-proof coating composition comprising:

[0109] Component A1: 1 g of biomass material with a cationic dendritic or network structure;

[0110] Preparation of cationic biomass material: 1.8 parts of the biomass material with a dendritic or network structure in Example 1 were added to 135 parts of a 0.12% NaOH aqueous solution, stirred at room temperature for 1.5 hours to obtain a biomass alkali solution, 50 parts of anhydrous ethanol were added to the biomass alkali solution, and then 1.8 parts of 2,3-epoxypropyltrimethylammonium chloride were added, and the mixture was stirred at 60°C for 6 hours. After the reaction was completed, the mixture was washed with water until neutral to obtain a cationic biomass material with a dendritic or network structure of 20 μm to 35 μm and a solid content of 1.25%.

[0111] Component B 10 parts: 9g PHA, 1g AKD;

[0112] Component C 10 parts: 4g palm wax, 4g etherified starch (substitution degree 0.1), and 2g montmorillonite.

[0113] The etherified starch in component C comes from Langfang Longteng New Materials Co., Ltd. (hydroxymethyl starch ether).

[0114] Oil-proof coating composition slurry: add 1g of biomass material with a dendritic or network structure, 9g of PHA, 1g of AKD, 4g of palm wax, 4g of modified starch, and 2g of montmorillonite into a stirring tank, then add 79g of deionized water, seal the stirring tank, vacuum stir for 30min, and discharge into a storage barrel to obtain a coating composition slurry.

[0115] Comparative Example 1

[0116] Component A1: 1 g of 3% cellulose nanofibers commercially available from Shengquan Group;

[0117] Component B 11 parts: 10g PHA, 1g AKD;

[0118] Component C 10 parts: 4g palm wax, 4g oxidized starch (substitution degree 0.2), and 2g montmorillonite.

[0119] The oxidized starch in component C comes from Zhucheng Xingmao Corn Development Co., Ltd.

[0120] Oil-proof coating composition slurry: add 1g cellulose nanofiber, 10g PHA, 1g AKD, 4g palm wax, 4g modified starch, and 2g montmorillonite into a stirring tank, then add 79g deionized water, seal the stirring tank, vacuum stir for 30min, and discharge into a storage barrel to obtain a coating composition slurry.

[0121] Comparative Example 2

[0122] Component B 15 parts: 15g PHA;

[0123] Component C 10 parts: 4g palm wax, 4g etherified starch, and 2g montmorillonite.

[0124] The etherified starch in component C comes from Langfang Longteng New Materials Co., Ltd. (hydroxymethyl starch ether).

[0125] Oil-proof coating composition slurry: 15 g PHA, 4 g palm wax, 4 g modified starch, and 2 g montmorillonite were added into a stirring tank, and then 75 g deionized water was added. The stirring tank was sealed, vacuum stirred for 30 min, and discharged into a storage barrel to obtain a coating composition slurry.

[0126] Test Case

[0127] The above preparation examples are specific test examples of coating the surface of paper to achieve the oil-proof function.

[0128] The coating composition slurry prepared in the above Examples 1-3 and Comparative Examples 1-2 was coated on a commercially available 300 g / m 2 The white cardboard was placed in an oven at 80℃ for drying, and then the coating and drying operations were repeated again (the total coating amount of different slurries is shown in Table 1). During drying, the paper was fixed to minimize the wrinkling and unevenness of the paper. The dried paper was calendered with a double steel roller calender heated to 180℃, with a pressure of 0.3-0.5MPa, to obtain an oil-proof paper sample. According to GBT22805.2-2008, the oil-proof grade of the oil-proof paper sample was tested using kit liquid, and the test results are shown in Table 1.

[0129] Table 1 Coating amount of different coating composition slurries coated on white cardboard

[0130]

[0131]

[0132] Table 2 Oil resistance rating of different coating composition slurries coated on white cardboard

[0133] name Oil resistance grade Example 1 kit6 Example 2 kit8 Example 3 kit12 Example 4 kit8 Comparative Example 1 kit2 Comparative Example 2 kit1

[0134] From Table 2 and Figure 2 It can be seen that the oil-proof paper obtained by coating the coating composition slurry of the present invention on white cardboard has an oil-proof grade of at least greater than kit 6 and can reach kit 12 at most, which is higher than the current commercial paper product oil-proof standard kit 7-8. The paper coated with the coating composition slurry of the present invention has an excellent oil-proof effect; at the same time, see Figure 2 As shown, the white cardboard and the oil-proof paper coated with the coating composition slurry in Example 3 were subjected to an oil penetration test. After 1 minute of dripping, obvious oil stains were visible on the front and back of the white cardboard, while obvious oil stains were visible on the front of the oil-proof paper (not coated with the coating composition slurry). After 1 hour, no oil stains were seen on the back, further indicating that the paper coated with the coating composition slurry of the present invention has an excellent oil-proof effect.

[0135] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. An oil-proof coating composition for paper products, characterized in that: The coating composition comprises: Component A: one or more of a biomass material having a dendritic or network structure or a cationized biomass material having a dendritic or network structure; Component B is one, two or more selected from the group consisting of polyhydroxyalkanoates, alkyl ketene dimers, polyglycolides, polylactides, copolymers of butylene adipate and butylene terephthalate, cellulose esters and cellulose ethers; Component C is one, two or more selected from beeswax, palm wax, vegetable wax, modified starch, montmorillonite and lamellar clay.

2. The oil-proof coating composition for paper products according to claim 1, characterized in that: In parts by weight, the oil-proof coating composition comprises 1-10 parts of component A, 5-20 parts of component B, and 5-20 parts of component C, and preferably consists of them. Preferably, the oil-proof coating composition comprises 3-6 parts of component A, 10-20 parts of component B, and 15-20 parts of component C, preferably consisting of them.

3. The oil-proof coating composition for paper products according to claim 1, characterized in that: When the component A is composed of biomass having a dendritic or network structure and a cationized biomass material having a dendritic or network structure, the mass ratio of the biomass having a dendritic or network structure to the cationized biomass material having a dendritic or network structure is (1-5):

1.

4. The oil-proof coating composition for paper products according to any one of claims 1 to 3, characterized in that The component B is selected from one, two or more of polyhydroxyalkanoates, alkyl ketene dimers, cellulose esters and cellulose ethers. Preferably, the component C is selected from one, two or more of beeswax, palm wax, modified starch and montmorillonite. Preferably, the modified starch is selected from one or more of oxidized starch, etherified starch and acetylated starch. Preferably, the degree of substitution of the modified starch is greater than or equal to 0.

1.

5. A method for preparing a coating composition slurry, characterized in that: The following steps are involved: The coating composition according to any one of claims 1 to 4 is mixed with a solvent to obtain a coating composition slurry.

6. The method for preparing the coating composition slurry according to claim 5, characterized in that: The mass ratio of the coating composition to the solvent is 1:(1-10). Preferably, the solvent is selected from one or a mixture of two or more of water, alcohol and ethyl acetate.

7. Use of the coating composition according to any one of claims 1 to 4 as an oil-proof coating for paper products.

8. A method for applying the oil-proof coating composition according to any one of claims 1 to 4 on the surface of a paper product, characterized in that: The steps include: The oil-proof coating composition slurry as described above is coated on at least one surface of a paper product material that can form a substrate to form an oil-proof coating layer.

9. The method for applying an oil-proof coating composition on the surface of a paper product according to claim 8, characterized in that: The coating amount is 10-30 g / m 2 , the drying temperature is 80-150°C.

10. A paper product with an oil-proof coating, comprising a substrate and an oil-proof coating located on at least one surface of the substrate.

Citation Information

Cited By

  • Method of starch degradation, greaseproof composite layer, and manufacturing method thereof

    TWI890650B